Exergy Evaluation of the 5 kW Downdraft Type Gasification System for its Application in a Cogeneration Process and the Effect Produced in the Synthesis Gas. - Ausay Oleas, Bryan Javier (2021)
The research results obtained on the effect that occurs on the properties of the synthesis gas obtained as a result of a biomass downdraft gasification process is presents in this paper, working with a cogeneration system internal to the reactor. A study of the previous related works was carried out, from which the dependent and independent variables necessary to evaluate the final quality of the process in the presence and absence of cogeneration were determined. For this, an experimental statistical design of four levels of type 4n was implemented, which allowed the performance of a comparative statistical analysis of the working states of the gasifier. On the other hand, an energy and exergy analysis of both states is presented where the potential of the gasification process to reuse thermal energy can be verified by incorporating a cogeneration system.